Group I mGluR Activation Enhances Ca(2+)-Dependent Nonselective Cation Currents and Rhythmic Bursting in Main Olfactory Bulb External Tufted Cells - Dong, Hong-Wei (Society for Neuroscience, 2009)
In the main olfactory bulb, activation of group I metabotropic glutamate receptors (mGluRs) by olfactory nerve stimulation generates slow (2 Hz) oscillations near the basal respiratory frequency. These oscillations arise in the glomerular layer and may be generated, in part, by the intrinsic neurons, the juxtaglomerular neurons. We investigated the physiological effects of group I mGluR agonists on one population of juxtaglomerular neurons, external tufted (ET) cells, which rhythmically burst at respiratory frequencies and synchronize the intraglomerular network. Electrophysiological studies in rat main olfactory bulb slices demonstrated that the mGluR agonist 3,4-dihydroxyphenylglycine (DHPG) amplified the strength of ET cell spike bursts, principally by increasing the number of spikes per burst. Voltage-clamp and Ca(2+)-imaging studies showed that DHPG elicits a Ca(2+)-dependent nonselective cation current (I(CAN)) in the dendrites of ET cells triggered by Ca(2+) release from internal stores. The DHPG effects on bursting and membrane current were attenuated by flufenamic acid and SKF96365, agents known to antagonize I(CAN) in a variety of neurons. DHPG also elicited slow membrane current oscillations and spikelets in ET cells when synaptic transmission and intrinsic membrane channels were inoperative. These findings indicate that DHPG may passively (by increasing burst strength) or actively (by increasing conductance of gap junctions) enhance the strength of electrical synapses between ET cells. Together, these findings indicate that activation of group I mGluRs on the dendrites of ET cells play a key role in the generation of slow rhythmic oscillation in the glomerular network, which is in turn tuned to sniffing of the animal in vivo.